Le computer-tailoring: solution potentielle pour optimiser les pratiques cliniques préventives de counselling en milieu clinique? - Boudreau, François (Can J Public Health, 2011)
Scientific literature shows that physicians who engage in clinical prevention practices (CPP) have an influence on population health. This is why they are encouraged to apply such practices to promote healthy lifestyle habits in their patients, such as exercise, a healthy diet, and smoking cessation. However, as revealed in a recent study published in the Canadian Journal of Public Health, lack of time is the main barrier for doctors in applying CPP. Following upon the results presented in their study, the authors suggest certain solutions that are likely to facilitate prevention practices. The goal of this commentary is to familiarize readers with another potential solution, relatively unknown in Canada, namely computer-tailoring. This innovative intervention method has the potential to facilitate prevention counselling because it provides a means of interacting with a large audience by formulating “customized” educational messages for each member.